RELATIONSHIP BETWEEN ULTRAVIOLET SENSITIVITY AND ABILITY TO PROPAGATE ULTRAVIOLET-IRRADIATED BACTERIOPHAGE - Hill, Ruth F. (1964)
Hill, Ruth F. (Columbia University, New York, N.Y.). Relationship between ultraviolet sensitivity and ability to propagate ultraviolet-irradiated bacteriophage. J. Bacteriol. 88:1283–1287. 1964.—Mutants with a reduced ability to propagate ultraviolet-damaged bacteriophage T(1) were isolated from Escherichia coli strain B/r. The change in this ability varied from a slight to a very marked loss; the greater the loss, the greater was the ultraviolet sensitivity of the mutant. Reduced ability to propagate irradiated T(1) appears to be the more sensitive index of genetic change, because in one mutant there was no significant reduction in ultraviolet resistance. In a converse study, second-step mutants with an increased ultraviolet resistance were obtained from a mutant of E. coli B. This mutant is both unable to propagate irradiated T(1) and very ultraviolet-sensitive. The increased ultraviolet resistance of the second-step mutants was not accompanied by an increased ability to propagate irradiated T(1).